Aceh Besar تحليل الأخطاء الصوتية في مهارة القراءة لدى طالبات الصف الثامن بمعهد إنسان قرآني - Syahda, Zakkia; Muslim, Buhori; Safariah, Safariah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Researcher analyzed vocal errors in the reading skill of class VIII students at Dayah Insan Qur'ani Aceh Besar after observing students' difficulties in pronouncing Arabic letters correctly. Among the reasons for this problem is the lack of analysis of the form of letters and sounds that are different from the Indonesian language, causing phonemic errors in Arabic letters. This study aims to identify the forms of vocal errors for class VIII students. The method used is a qualitative method, namely descriptive analysis that explains data and takes summary with words. The data collection technique is done by recording words using a voice recorder. The search results obtained show that there are thirty-eight errors that are divided into twelve types of errors. The highest number of errors are in the short neglect of harakat, then followed by the neglect of long harakat, replace the sound of 'ain with hamzah, replace the sound of ha with Ha, replace the sound of Ha with ha, replace the sound of qaf with kaf, replace the sound of dzal with zai, replace the sound of tha with ta, replace the sound of hamzah with 'ain, replace the sound of sin with shad, replace the sound of shad with sin, and replace the sound of ta with tha.